Analysis of accidents of the WWER-1000 reactor in which emergency cooling heat exchangers operate - Pyrohov, Tymofii; Korolev, Alexander; Inyushev, Vladislav; Kurov, Volodymyr (Technology audit and production reserves, 2020)
The object of research is the emergency operation modes of the WWER-1000 nuclear installation elements, which also use emergency cooling heat exchangers. The analytical studies carried out are based on an analysis of the operating documentation of the above-mentioned nuclear installation. An analysis of the elements of the emergency core cooling system, which includes emergency cooling heat exchangers, has been carried out. This analysis has shown that in order to localize the accidents of the WWER-1000 reactor unit, the coolant that comes out of the leak is collected in the tank of the plant and from there is pumped by pumps through the above-mentioned heat exchangers. This ensures that the heat of the coolant escaping from the leak is removed and the reactor core is effectively cooled using already cooled water. As a result of a comparative analysis of design accidents at the WWER-1000 reactor unit, it has been established that the emergency core cooling system is involved in accidents related to a rupture of the first and second reactor circuit pipelines within the containment. Such accidents include small, medium and large leaks in the primary circuit as well as ruptures in the steam line or feed water pipeline of the steam generator (within the containment). A detailed review of the parameters of the coolant that flows out of the leak and into the tip-tank shows that the most conservative accident involving emergency cooling heat exchangers is a «Large leak mode. Bilateral rupture of the main circulation pipeline DN 850 mm». In this accident, the temperature of the coolant in the tip-tanks reaches 110 °С and subsequently enters the inter-tube space of the heat exchangers. Currently, there is an urgent task to justify the safe operation of nuclear power plant equipment and emergency cooling heat exchangers in particular. The results of the research can serve as baseline data for determining the thermal stress state of the above-mentioned heat exchangers in accidents of the WWER-1000 nuclear installation.